Exploring the patterns of availability and provision of sexual and reproductive health services to young people in primary healthcare centers in Ebonyi state, Nigeria - Joy Nkeiruka Ozughalu; Ozioma Patricia Nwankpa; Chinyere Ojiugo Mbachu; Obinna Onwujekwe (BMC Health Services Research)
Abstract Background Adolescents and young people represent a significant portion of the population in Nigeria. Thus, addressing their unique sexual and reproductive health (SRH) needs is imperative for overall national health outcomes, especially given the limited availability of youth friendly services. This study aimed to identify the factors that influence availability and provision of SRH services to young persons in Ebonyi State, Southeast Nigeria. Methods A cross-sectional quantitative study was used to explore the patterns of health service availability and provision among healthcare providers in primary healthcare centers. Descriptive analysis was used to examine respondents’ socio-demographic characteristics and their provision of differential treatment based on gender and age. Rao-Scott chi-squared test assessed the relationship between the two outcome variables-health service availability and provision. Multiple logistic regression, adjusted for clustering at the facility level, was used to examine associations between dependent variables and independent variables, including age, gender, location, years of formal education, and training in providing youth-friendly sexual and reproductive health services. Results Rural areas reported higher service availability than urban areas, likely due to targeted national health programs. However, service provision remained inconsistent, especially for post-abortion care and support for survivors. Higher provider education was positively linked to both availability and provision. Youth-friendly training improved reported availability but did not enhance actual service delivery. Conclusion While targeted interventions have improved service availability in rural areas, significant gaps remain in actual service provision, particularly for sensitive SRH services. Enhancing provider education and addressing systemic barriers to youth-friendly care are essential to translating availability into meaningful access and quality service delivery.